Cultural and Personality Predictors of Facebook Intrusion: A Cross-Cultural Study - Błachnio, Agata; Przepiorka, Aneta; Benvenuti, Martina; Cannata, Davide; Ciobanu, Adela M.; Senol-Durak, Emre; Durak, Mithat; Giannakos, Michail N.; Mazzoni, Elvis; Pappas, Ilias O.; Popa, Camelia; Seidman, Gwendolyn; et al. (Frontiers in Psychology, 2016)
The increase in the number of users of social networking sites has inspired intense efforts to determine intercultural differences between them. The main aim of the study was to investigate the cultural and personal predictors of Facebook intrusion. A total of 2,628 Facebook users from eight countries took part in the study. The Facebook Intrusion Questionnaire, the Ten-Item Personality Measure, and the Singelis Scale were used. We found that two variables related to Country were significantly related to Facebook intrusion: uniqueness (negatively) and low context (positively); of the personality variables, conscientiousness and emotional stability were negatively related to the dependent variable of Facebook intrusion across different countries, which may indicate the universal pattern of Facebook intrusion. The results of the study will contribute to the international debate on the phenomenon of social networking sites (SNS).